КӨРКЕМ ӘДЕБИЯТ – СӨЙЛЕЎ МӘДЕНИЯТЫМЫЗДЫ ЖАҚСЫЛАЎ ҚУРАЛЫ СЫПАТЫНДА - Пазылов, М. (FAN va JAMIYAT, 2016)
The article is devoted to the analysis of some words, used in the speech of modern language. It contains the views about the role of literary works improving the culture of speech on the example of the novel in trilogy «Unhappy» by T.Kayipbergenov.